Optimization Of Beef Cattle Sales Throught The Integration Of Digital Marketing And Pre-Order Systems: A Case Study In Tuban Regency - Fahlefi Irhamni, Ahmad; Nur Eritrina, Hana; Priyanto, Bambang; Gagung, Joko (JALOW | Journal of Agribusiness and Local Wisdom, 2026)
This study aims to analyze the optimization of beef cattle sales through the integration of digital marketing strategies and a pre-order system, compare sales performance, and evaluate supply chain efficiency and business financial feasibility at PS Tunas Muda, Tuban Regency. The research method used was descriptive quantitative with a data collection period from December 2025 to January 2026. Data analysis used the Independent T-Test to compare sales volume and financial feasibility analysis using the indicators of R/C Ratio, B/C Ratio, and Break Even Point (BEP). The results showed a significant increase in sales volume from 14 heads (conventional) to 23 heads (digital pre-order) with a significance value of 0.015 (p < 0.05). Financial analysis recorded a profit of IDR 47,129,646 with an R/C Ratio of 1.08 and a B/C Ratio of 0.08. The pre-order system successfully shortened the supply chain, resulting in a farmer’s share of 100% with a marketing margin of 0%. The integration of pre-order-based digital marketing effectively increased sales volume and created economic efficiency by eliminating the role of intermediaries in livestock distribution.